Answer:
f^-1(x) = (x -2)/3
Step-by-step explanation:
To find the inverse function, swap x and y, then solve for y.
y = 3x +2 . . . . given function
x = 3y +2 . . . . inverse relation
x -2 = 3y . . . . subtract 2
(x -2)/3 = y . . . divide by 3
f^-1(x) = (x -2)/3 . . . . in functional form
Answer:
25
Step-by-step explanation:
5^2 = 25
5 * 5 = 25
Answer:
5 hours
Step-by-step explanation:
if 10 hours cover 650 miles, 1 hour covers 65 miles. When you divide 325 by 65 you get 5 hours.
an easier way is, 650 ÷ 2 = 325 miles, likewise when 10 ÷ 2 = 5 hours
Answer:
acute triangle
Step-by-step explanation:
A triangle with all angles less than 90 degrees has all angles that are acute.
Acute angles are less than 90 degrees